Editing the duplicated insulin-like growth factor binding protein-2b gene in rainbow trout (Oncorhynchus mykiss). Issue 1 (December 2018) - Cleveland, Beth; Yamaguchi, Ginnosuke; Radler, Lisa; Shimizu, Munetaka
Abstract In salmonids, the majority of circulating insulin-like growth factor-I (IGF-I) is bound to IGF binding proteins (IGFBP), with IGFBP-2b being the most abundant in circulation. We used CRISPR/Cas9 methodology to disrupt expression of a functional IGFBP-2b protein by co-targeting for gene editing IGFBP-2b1 and IGFBP-2b2 subtypes, which represent salmonid-specific gene duplicates. Twenty-four rainbow trout were produced with mutations in the IGFBP-2b1 and IGFBP-2b2 genes. Mutant fish exhibited between 8–100% and 2–83% gene disruption for IGFBP-2b1 and IGFBP-2b2, respectively, with a positive correlation (P < 0.001) in gene mutation rate between individual fish. Analysis of IGFBP-2b protein indicated reductions in plasma IGFBP-2b abundance to between 0.04–0.96-fold of control levels. Plasma IGF-I, body weight, and fork length were reduced in mutants at 8 and 10 months post-hatch, which supports that IGFBP-2b is significant for carrying IGF-I. Despite reduced plasma IGF-I and IGFBP-2b in mutants, growth retardation in mutants was less severe between 10 and 12 months post-hatch (P < 0.05), suggesting a compensatory growth response occurred. These findings indicate that gene editing using CRISPR/Cas9 and ligand blotting is a feasible approach for characterizing protein-level functions of duplicated IGFBP genes in salmonids and is useful to unravel IGF-related endocrine mechanisms.